2021
DOI: 10.3390/ijerph18020362
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Participation and Performance of 2067 100-km Ultra-Marathons Worldwide

Abstract: This study aimed to analyze the number of successful finishers and the performance of the athletes in 100-km ultra-marathons worldwide. A total of 2067 100-km ultra-marathon races with 369,969 men and 69,668 women competing between 1960 and 2019 were analyzed, including the number of successful finishers, age, sex, and running speed. The results showed a strong increase in the number of running events as well as a strong increase in the number of participants in the 100-km ultra-marathons worldwide. The perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 43 publications
2
21
0
Order By: Relevance
“…Participation has been increasing since 2010, with a decrease in 2020 due to the pandemic situation caused by SARS-CoV-2 [21]. Similar results were previously shown [5,13]. Increases in ultra-mara-…”
Section: More Athletes But Slowersupporting
confidence: 78%
“…Participation has been increasing since 2010, with a decrease in 2020 due to the pandemic situation caused by SARS-CoV-2 [21]. Similar results were previously shown [5,13]. Increases in ultra-mara-…”
Section: More Athletes But Slowersupporting
confidence: 78%
“…An increase in participation will not necessarily lead to an improvement in performance. This has also been shown when all 100-km ultra-marathons held since 1960 were analyzed [ 28 ]. There was a substantial increase in both the number of running events and in the number of participants, where performance started to decline after the year 2000 for runners younger than 70 years, with an improvement only in runners older than 70 years [ 28 ].…”
Section: Discussionmentioning
confidence: 59%
“…This has also been shown when all 100-km ultra-marathons held since 1960 were analyzed [ 28 ]. There was a substantial increase in both the number of running events and in the number of participants, where performance started to decline after the year 2000 for runners younger than 70 years, with an improvement only in runners older than 70 years [ 28 ]. Therefore, future improvement in the elite ultra-marathoners’ performance can be expected only in races with strict criteria for selection and strict cut-off times during the race.…”
Section: Discussionmentioning
confidence: 59%
“…In some instances, male master marathoners older than 90 years can complete a 6-h-run or even a 12-h-run . Recently, it has been reported that master runners older than 80or 90 years finished a 100-km ultra-marathon (Stohr et al, 2021).…”
Section: Editorial On the Research Topicmentioning
confidence: 99%